Implementation of low-intensity aerobic exercise to prevent functional balance disorders and fall risk among the elderly - Setiawan, Cahyo; Sari, Apriliyan Yunita; Wijayanti, Arvita Anggun; Al Ishom, Mochammad Nawfal Azif (Community Empowerment, 2025)
Balance disorders in the elderly are a significant public health problem, often leading to a risk of falls and a decline in quality of life. The purpose of this activity was to provide education about low-intensity aerobic exercise to prevent functional balance disorders and the risk of falls in the elderly. The methods used included socialization, education, and direct practice. The results of the activity showed a significant increase of 15 points based on the Berg Balance Scale (BBS) score and improvement in the Timed Up and Go (TUG) test results to 9 seconds. This shows the effectiveness of low-intensity aerobic exercise in improving balance and mobility. In addition, the socialization and education activities showed an increase in participants' understanding of fall risk by 85%. This program not only succeeded in reducing the risk of falls but also increased the self-confidence and quality of life of the elderly.